Biotechnology for sustainable agriculture : emerging approaches and strategies - Singh, Ram Lakhan; Mondal, Sukanta (Woodhead Publishing, 2017)
Biotechnology for Sustainable Agriculture: Emerging Approaches and Strategies is an outstanding collection of current research that integrates basic and advanced concepts of agricultural biotechnology with future development prospects. Using biotechnology with sustainable agriculture effectively contributes to gains in agricultural productivity, enhanced food security, reduced poverty and malnutrition, and more ecologically sustainable means of food production. Written by a panel of experts, this book is unique in its coverage of the broad area of biotechnology for sustainable agriculture. It includes intriguing topics and discussions of areas such as recombinant DNA technology and genetic engineering.